Absorption spectrum and absorption cross sections of the 2ν1 band of HO2 between 20 and 760 Torr air in the range 6636 and 6639 cm−1. (May 2018) - Assaf, Emmanuel; Liu, Lu; Schoemaecker, Coralie; Fittschen, Christa
Highlights: The absorption spectrum of HO2 radicals in the range 6636–6639 cm −1 has been measured at different pressures. Absolute absorption cross sections of HO2 radicals have been measured in the range 20–760 Torr air at the wavelength of the most intense transition around 6638.2 cm −1 . These data will enable the quantification of HO2 radicals in atmospheric simulation chambers. Abstract: The absorption spectrum of HO2 radicals has been measured in the range 6636–6639 cm −1 at several pressures between 20 and 760 Torr of air. Absolute absorption cross sections of the strongest line at around 6638.2 cm −1 have been determined from kinetic measurements, taking advantage of the well known rate constant of the self-reaction. Peak absorption cross sections of 22.6, 19.5, 14.4, 7.88, 5.12 and 3.23 × 10 −20  cm 2 were obtained at 20, 50, 100, 200, 400 and 760 Torr, respectively. By fitting these data, an empirical expression has been obtained for the absorption cross section of HO2 in the range 20–760 Torr air: σ 6638.2cm -1  = 1.18 × 10 −20  + (2.64 × 10 −19  × (1–exp (−63.1/p (Torr))) cm 2 .